2024
DOI: 10.1109/tcss.2022.3215528
|View full text |Cite
|
Sign up to set email alerts
|

Complaint and Severity Identification From Online Financial Content

Abstract: The automatic detection of financial complaints can benefit businesses and online merchants. Compared to manually tagged complaints, they can use this information to monitor and address issues and effectively route them to appropriate teams. This can also promote greater transparency and accountability when dealing with consumer financial products and services, strengthening the firm's brand value. In linguistic studies, complaints have been classified into severity categories based on the level of risk the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The subsequent use of our workflow intends to mitigate this issue, but still relies on the results of proximity-based keyword-based approaches as a reference set which may limit how new patterns of IPFA are discovered. Like other HCI studies based on self-reported data, complainants may overstate certain aspects of their financial history due to social desirability bias [91] or to elicit empathy and alleviate financial burdens [49]. People with negative experiences may be more inclined to write formal complaints [59], while others may fear repercussions or societal stigma [44,90].…”
Section: Further Insight Into Technology-enabled Financial Abusementioning
confidence: 99%
“…The subsequent use of our workflow intends to mitigate this issue, but still relies on the results of proximity-based keyword-based approaches as a reference set which may limit how new patterns of IPFA are discovered. Like other HCI studies based on self-reported data, complainants may overstate certain aspects of their financial history due to social desirability bias [91] or to elicit empathy and alleviate financial burdens [49]. People with negative experiences may be more inclined to write formal complaints [59], while others may fear repercussions or societal stigma [44,90].…”
Section: Further Insight Into Technology-enabled Financial Abusementioning
confidence: 99%
“…This necessitates a more efficient complaint detection approach, as exhibited in recent studies (Preotiuc-Pietro et al, 2019;Singh et al, 2022a) that have successfully automated the classification of binary complaints and their associated severity levels. Emotion recognition (ER) and sentiment recognition (SR) play vital roles in understanding the affective aspects of customer complaints Singh et al, 2023a). In this transition towards automation, inspiration can be drawn from multitask learning (Caruana, 1997)-an approach that mirrors our inherent human ability to learn multiple tasks simultaneously and transfer knowledge across them.…”
Section: Introductionmentioning
confidence: 99%